"It can lift someone from poverty": Imagined futures in the Sierra-Le-onean diamond market. Issue 2 (April 2018) - Engwicht, Nina
Highlights: Scholarly and policy-oriented research needs to take into account artisanal miners' expectations of the future. Projections of upward social mobility inform miners' economic strategies in the present. If these remain poorly understood, policies cannot adequately address the needs of artisanal mining communities. Abstract: This article aims to draw attention to the role of the future in artisanal mining. It argues that in order to understand the dynamics of artisanal mining, research must understand miners' imaginaries of a better future which inform their economic strategies in the present. Drawing on Jens Beckert's (2016) concepts of fictional expectations and imagined futures, the article investigates projections of the future and strategies of future-making in the Sierra Leonean diamond market. If these expectations remain poorly understood, development policies will not be able to address the needs of mining communities.